Temporary work in the post-industrial era - Świątkowski, Andrzej Marian (Temporary employment as an atypical form of employment: No. 19/2022, 2022)
The author reflects on the usefulness of temporary work in the post-industrial era. He believes that this form of atypical employment can be replaced by electronic employment technologies.